Efficacy of left subclavian artery revascularization strategies during thoracic endovascular aortic repair in patients with type B dissection: A single-center experience of 105 patients - Wu, Xiangyang; Li, Yongnan; Zhao, Yinglu; Zhu, Yilin; Wang, Shixiong; Ma, Qi; Liu, Debin; Gao, Bingren; Wei, Shilin; Wang, Weifan (Frontiers in Cardiovascular Medicine, 2023)
Background: For Stanford type B aortic dissection patients with insufficient proximal anchoring area. Left subclavian artery (LSA) revascularization combined with Thoracic endovascular aortic repair (TEVAR) is necessary to reduce postoperative complications. However, it remains unclear the efficacy and safety of different LSA revascularization strategies. This study aims to compare these strategies, so as to provide clinical basis for the selection of LSA revascularization methods. Methods: 105 patients with type B aortic dissection treated by TEVAR combined with LSA reconstruction in the Second Hospital of Lanzhou University from March 2013 to March 2020 were statistically analyzed. According to the method of LSA reconstruction, they were divided into four groups: Carotid subclavian bypass (CSB) group (n=41), Chimney grafts (CG) group (n=29), Single-branched stent graft (SBSG) group (n=21), Physician-Made Fenestration (PMF) group (n=14). Baseline information, perioperative, operation, postoperative and follow-up data of the four groups of patients were collected and analyzed. Results: The success rate of the four groups was 100%, CSB+TEVAR was greatly used in emergency settings compared with other three groups (p<0.05). Estimate blood loss, contrast agent volume, fluoroscopy time, operative time, and symptoms of limb ischemia during follow-up in the four groups were significantly different (P< 0.05). Pairwise comparison among groups showed that the estimate blood loss and operative time in CSB group were the highest (adjusted P< 0.0083; P< 0.05). According to the amount of contrast volume and the duration of fluoroscopy, SBSG group> PMF group >CG group> CSB group. The incidence of limb ischemia symptoms was the highest in the PMF group (28.6%) during the follow-up period. The incidence of complications (except symptoms of limb ischemia) during the perioperative period and the follow-up period among the four groups were similar (P> 0.05), the median follow-up time of CSB group, CG group, SBSG group and PMF group was significantly different (P< 0.05), and CSB group had the longest follow-up time. Conclusion: Our single center experience found that all these strategies could effectively and safely restore LSA perfusion with comparable complications for patients with Type B aortic dissection. Different LSA revascularization techniques have its own advantages and disadvantages.